2012
DOI: 10.1080/00087114.2012.678079
|View full text |Cite
|
Sign up to set email alerts
|

Karyological studies of the genusOnobrychisMill. and the related generaHedysarumL. andSartoriaBoiss. & Heldr. (Fabaceae, Hedysareae) from Turkey

Abstract: Nine chromosome counts in several genera of the tribe Hedysareae from Turkey, six species of Onobrychis, two species of Hedysarum and one species of Sartoria, were reported and all karyotypes were prepared. Six of them are new. One of the other three reports is a confirmation of polyploidy, another report is a confirmation of chromosome count and the last report is a confirmation of both chromosome count and karyotype morphology. Except for karyotype of O. altissima, all karyotypes were presented in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
5
18
0
1
Order By: Relevance
“…In Faboideae, the occurrence of tetraploids, mainly in species belonging to the group showing x = 7, was described in the genus Onobrychis Adans by Hejazi et al (2010). Arslan et al (2012) also discuss the The species with n = 12 and n = 13 suggest also the occurrence of either aneuploidy or dysploidy in the evolutionary history of Senna, as previously discussed by Souza and Benko-Iseppon (2004) for the genus Cassia s.l., which includes Senna along with Chamecrista and Cassia. A detailed description of karyotypes is important to elucidate what kind of chromosomal changes might have happened.…”
Section: Resultsmentioning
confidence: 99%
“…In Faboideae, the occurrence of tetraploids, mainly in species belonging to the group showing x = 7, was described in the genus Onobrychis Adans by Hejazi et al (2010). Arslan et al (2012) also discuss the The species with n = 12 and n = 13 suggest also the occurrence of either aneuploidy or dysploidy in the evolutionary history of Senna, as previously discussed by Souza and Benko-Iseppon (2004) for the genus Cassia s.l., which includes Senna along with Chamecrista and Cassia. A detailed description of karyotypes is important to elucidate what kind of chromosomal changes might have happened.…”
Section: Resultsmentioning
confidence: 99%
“…From these and other reports (e.g. Fedorov 1969;Goldblatt 1981aGoldblatt , 1981bGoldblatt , 1984Goldblatt , 1985Goldblatt , 1988Romano et al 1987;Goldblatt and Johnson 1991;Diaz-Lifante et al 1992;Tamas 2006;Ranjbar et al 2009aRanjbar et al , 2010Hesamzadeh Hejazi and Ziaei Nasab 2010;Ranjbar et al 2010c;Ranjbar et al 2010d;Ranjbar et al 2010f;Arslan et al 2012) it is evident that the chromosome count is known for just over a quarter of the species. Two basic chromosome numbers (x = 7 and x = 8) and three ploidy levels (2n = 2x = 14, 2n = 4x = 28, 2n = 8x = 56 and 2n = 2x = 16, 2n = 4x = 32) are present in the genus Onobrychis.…”
Section: Introductionmentioning
confidence: 97%
“…Accessions of O. altissima, for instance, have 2n = 14 (Arslan et al, 2012) and others have 2n = 28 (Hejazi et al, 2010), while a variation of 2n = 22, 27, 28, 29 was found in O. viciifolia. After Ranjbar et al (2010), O. altissima is considered to be closely related to the cultivated sainfoin (O. viciifolia) and may be a progenitor of it, while, based on morphological similarity, a close relationship between the 2 species was postulated by Hedge (1970).…”
Section: Karyotype Evolution In Hedysareaementioning
confidence: 99%
“…Astragalus and Chesneya of the related Astragalean clade (Sepet et al, 2011) also have a basic number of n = 8. A count of 2n = 18 in Sulla coronaria (as Hedysarum coronarium) is known (Issolah et al, 2006), such that Arslan et al (2012) also consider n = 9 to be a possible basis chromosome number in Hedysarum s. l. The count 2n = 16 was also found in the genus Sartoria (not sampled here; Arslan et al, 2012). Hedysarum s. s. (the clade containing the genus type H. alpinum) has n = 7, apart from 1 count of n = 8 for an accession of H. alpinum.…”
Section: Karyotype Evolution In Hedysareaementioning
confidence: 99%